Annual Plan 1972-73 - Planning Commission (Planning Commission, 1972)
The Mid-term Appraisal of the Fourth Plan which was brought out in December 1971 indicated that the necessary adjustments will be introduced in an orderly way during the formulation of the Annual Plan, 1972-73 to give further impetus to our objective of growth with social justice. The four main directions in which increased effort was identified as necessary in the Appraisal document were better plan implementation and increased outlays to correct emerging short-falls, resource mobilisation in the Centre and in the States, increased self-reliance and larger outlays on schemes designed to promote employment and social justice.
Government of India Planning Commission
Government of India Planning Commission